Liposomal Delivery Improves the Efficacy of Prednisolone to Attenuate Renal Inflammation in a Mouse Model of Acute Renal Allograft Rejection. Issue 4 (April 2020) - van Alem, Carla M.A.; Schmidbauer, Martina; Rong, Song; Derlin, Katja; Schmitz, Jessica; Bräsen, Jan H.; Thorenz, Anja; Chen, Rongjun; Ruben, Jurjen M.; Winter, Elizabeth M.; Schilperoort, Maaike; Kooijman, Sander; et al.
Abstract : Background: Systemic exposure to high-dose corticosteroids effectively combats acute rejection after kidney transplantation, but at the cost of substantial side effects. In this study, a murine acute renal allograft rejection model was used to investigate whether liposomal-encapsulated prednisolone (LP) facilitates local exposure to enhance its therapeutic effect. Methods: Male BalbC recipients received renal allografts from male C57BL/6J donors. Recipients were injected daily with 5 mg/kg cyclosporine A and received either 10 mg/kg prednisolone (P), or LP intravenously on day 0, 3, and 6, or no additional treatment. Functional magnetic resonance imaging (fMRI) was performed on day 6 to study allograft perfusion and organs were retrieved on day 7 for further analysis. Results: Staining of polyethylene-glycol-labeled liposomes and high performance liquid chromatography analysis revealed accumulation in the LP treated allograft. LP treatment induced the expression of glucocorticoid responsive gene Fkbp5 in the allograft. Flow-cytometry of allografts revealed liposome presence in CD45 + cells, and reduced numbers of F4/80 + macrophages, and CD3 + T-lymphocytes upon LP treatment. Banff scoring showed reduced interstitial inflammation and tubulitis and fMRI analysis revealed improved allograft perfusion in LP versus NA mice. Conclusions: Liposomal delivery of prednisolone improved renal bio-availability, increased perfusion and reduced cellular infiltrate in the allograft, when compared with conventional prednisolone. Clinical studies should reveal if treatment with LP results in improved efficacy and reduced side effects in patients with renal allograft rejection. Abstract : Supplemental Digital Content is available in the text.